2020
DOI: 10.1021/acsnano.0c05610
|View full text |Cite
|
Sign up to set email alerts
|

Bright Aggregation-Induced Emission Nanoparticles for Two-Photon Imaging and Localized Compound Therapy of Cancers

Abstract: Photodynamic therapy (PDT), a noninvasive therapeutic strategy for cancer treatment, which always suffers from the low reactive oxygen species (ROS) yield of traditional organic dyes. Herein, we present lipid-encapsulated aggregation-induced emission nanoparticles (AIE NPs) that have a high quantum yield (23%) and a maximum two-photon absorption (TPA) cross-section of 560 GM irradiated by near-infrared light (800 nm). The AIE NPs can serve as imaging agents for spatiotemporal imaging of tumor tissues with a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 54 publications
0
69
0
Order By: Relevance
“…In addition, we further verified that TFMN or TTFMN could first take one electron from the environmental hydroxyl anion and turn into intermediate radical anions ( • PS − ) before they transfer electron to O 2 , with the Gibbs free energy changes of −73.21 and −90.07 kcal mol −1 for TFMN and TTFMN calculated by PWPB95‐D3/def2‐TZVP using the quantum mechanism package ORCA 4.1.1 (Figure S14 , Supporting Information). [ 49 , 50 ] Similarly, the more negative value of TTFMN accounted for its better type‐I ROS generation performance. Consequently, it is reasonable to conclude that the type‐I ROS generation process of TFMN and TTFMN is consistent with the previously reported mechanism, [ 7 , 51 ] meaning that triplet TFMN or TTFMN first takes one electron from the environmental hydroxyl anion, and subsequently transfers the electron to O 2 , accompanying with the generation of • O 2 − , which could be further transformed into • OH via secondary reactions ultimately (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we further verified that TFMN or TTFMN could first take one electron from the environmental hydroxyl anion and turn into intermediate radical anions ( • PS − ) before they transfer electron to O 2 , with the Gibbs free energy changes of −73.21 and −90.07 kcal mol −1 for TFMN and TTFMN calculated by PWPB95‐D3/def2‐TZVP using the quantum mechanism package ORCA 4.1.1 (Figure S14 , Supporting Information). [ 49 , 50 ] Similarly, the more negative value of TTFMN accounted for its better type‐I ROS generation performance. Consequently, it is reasonable to conclude that the type‐I ROS generation process of TFMN and TTFMN is consistent with the previously reported mechanism, [ 7 , 51 ] meaning that triplet TFMN or TTFMN first takes one electron from the environmental hydroxyl anion, and subsequently transfers the electron to O 2 , accompanying with the generation of • O 2 − , which could be further transformed into • OH via secondary reactions ultimately (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, strengthening the D-A geometry, various two-photon capable AIEgens are developed with strong and stable fluorescence (15,16). 24,61…”
Section: Scheme 1 Rim Phenomenon Of Aie Emission (A)mentioning
confidence: 99%
“…In summary, micellar CE6 potentially functions as a dual-function PS for angiography and PDT to promote their delivery in the tumor microenvironment. At the same time, Li et al reported liposome encapsulated aggregation induced emission iuminogen nanoparticles (AIE nanoparticles) [ 170 ]. Under near-infrared light (800 nm), a high quantum yield (23%) and a maximum two-photon absorption (TPA) cross section of 560 GM were observed.…”
Section: Nanoparticle-based Drug Delivery For Melanoma Therapeuticmentioning
confidence: 99%